(untitled) (Velocity: Journal of Sharia Finance and Banking, 2026)
This study reviews recent research on the contribution of Islamic philanthropy, including zakat, infaq, sadaqah, and waqf (ZISWAF), to community-based economic development in Indonesia. Using a systematic literature review (SLR) approach, the study examines peer-reviewed publications published between 2020 and 2025 that focus on ZISWAF governance, productive financing programs, and digital innovations. The findings show that productive zakat programs, when accompanied by mentoring, entrepreneurship training, and microfinance support, can improve beneficiaries’ income, strengthen business sustainability, and enhance social mobility. Productive waqf has also emerged as a promising instrument for long-term economic development, particularly when supported by professional governance and effective asset management. In addition, the adoption of digital technologies, such as fintech platforms, online payment systems, and real-time reporting tools, has improved transparency, operational efficiency, and public trust in Islamic philanthropic institutions. Despite these positive developments, several challenges remain, including disparities in digital literacy, limited managerial capacity among waqf administrators, and the absence of standardized frameworks for measuring socioeconomic impact. The review further highlights that existing studies tend to examine ZISWAF instruments separately, with limited attention given to integrated approaches that connect Islamic philanthropy with inclusive and sustainable community development. The study concludes that Islamic philanthropy has significant potential to promote grassroots economic empowerment when supported by sound governance, digital innovation, and collaborative ecosystem-based strategies. Future research should focus on developing integrated ZISWAF models, conducting longitudinal impact assessments, and identifying scalable mechanisms for community economic development.